Subject specific finite element modeling of periprosthetic femoral fracture using element deactivation to simulate bone failure. Issue 6 (June 2015) - Miles, Brad; Kolos, Elizabeth; Walter, William L.; Appleyard, Richard; Shi, Angela; Li, Qing; Ruys, Andrew J.
Highlights: The development of methodology to simulate bone failure and aid prediction of fracture load in addition to fracture risk characterization for peri-prosthetic femoral fracture (PFF). Using subject-specific finite element models and element deactivation. Element deactivation was used to simulate a crack path in the bone tissue based on a threshold of strain. Crack mode for the biphasic models was very similar to the experimental testing crack mode, with a similar shape of the crack, and similar crack path. Abstract: Subject-specific finite element (FE) modeling methodology could predict peri-prosthetic femoral fracture (PFF) for cementless hip arthoplasty in the early postoperative period. This study develops methodology for subject-specific finite element modeling by using the element deactivation technique to simulate bone failure and validate with experimental testing, thereby predicting peri-prosthetic femoral fracture in the early postoperative period. Material assignments for biphasic and triphasic models were undertaken. Failure modeling with the element deactivation feature available in ABAQUS 6.9 was used to simulate a crack initiation and propagation in the bony tissue based upon a threshold of fracture strain. The crack mode for the biphasic models was very similar to the experimental testing crack mode, with a similar shape and path of the crack. The fracture load is sensitive to the friction coefficient at the implant–bony interface. The development of a novel technique to simulate bone failure by element deactivation of subject-specific finite element models could aid prediction of fracture load in addition to fracture risk characterization for PFF.